Superconformal indices on S1×(S5/Zp) - Andreas Gustavsson (Nuclear Physics B, 2019)
We obtain generating functions associated to the abelian superconformal indices for 6d (1,0) tensor and hypermultiplets on S1×(S5/Zp). We extract the superconformal indices and their high and low temperature behaviors. We consider round and generically squashed S5 in turn. We show that the unsquashed limit of the superconformal indices is smooth. We examine S-duality in the large p limit that acts by exchanging the Hopf circle with the temporal circle.